Socialization Making Eco-Friendly Compost Use Bacteria Photosynthesis (PSB) in the Village Prapen, Central Lombok - Halina Talia; irtiqa17; Salsabila Rahmawati; Muhammad Naufal Haidar Aidin (Yayasan Siti Widhatul Faeha, 2026)
This community service activity aimed to enhance the knowledge and practical skills of the Prapen Village community, particularly the PKK women’s group, regarding the production and use of Photosynthetic Bacteria (PSB) as an eco-friendly organic fertilizer. The program combined theoretical explanation, hands-on practice, demonstration of fermentation stages, and distribution of PSB samples and plant seeds. Data were collected through observation and participant questionnaires. The results show that 84.6% of participants had no prior knowledge of PSB, but understanding increased significantly after the activity, with 98% stating that the material was very important and applicable. Participants demonstrated strong motivation to implement PSB at home, supported by clear and easily understood learning materials. The introduction of PSB is scientifically relevant because it improves soil fertility, nutrient availability, and plant health while reducing dependence on chemical fertilizers. This activity is expected to strengthen sustainable household agriculture and promote environmentally friendly practices within the community. Follow-up mentoring is recommended to ensure long-term adoption and practical application of PSB technology